Cognitive Processing Therapy for the Treatment of Acute Stress Disorder Following Sexual Assault: A Randomised Effectiveness Study. Issue 4 (7th March 2017) - Nixon, Reginald D.V.; Best, Talitha; Wilksch, Sarah R.; Angelakis, Samantha; Beatty, Lisa J.; Weber, Nathan
Abstract : The effectiveness of individually administered cognitive processing therapy (CPT) when compared with treatment as usual (TAU) in a community sexual assault centre was tested. Trauma survivors with acute stress disorder (ASD) following sexual assault were randomised to either CPT ( n = 25) or TAU ( n = 22), and assessed at pretreatment, posttreatment, and 3-, 6- and 12-month follow-up. Both groups demonstrated large reductions in PTSD and depression symptoms following treatment, and these gains were maintained over the course of follow-ups (Cohen's d s for PTSD symptom reductions ranging between 0.76 to 1.45). Although smaller and not always consistent, between-group effect sizes typically favoured CPT. Effect sizes ( d ) ranged between 0.13–0.50 for posttraumatic stress and 0.13–0.41 for depression over the course of follow-ups. Independent assessment of PTSD severity indicated more CPT participants reached good end-state functioning at 12-month follow-up (50%) than TAU (31%). Although both treatments were effective, there were some indications that CPT led to better outcomes relative to therapists delivering their usual therapy. The present study demonstrates that evidence-based, trauma-focused therapy such as CPT can be effective when delivered as an early intervention in a routine mental health setting.